2014
DOI: 10.4103/0972-2327.132625
|View full text |Cite
|
Sign up to set email alerts
|

A clinical profile of patients with Parkinson′s disease and psychosis

Abstract: Aims:The aim of the study was to study the clinical profile of the patients with Parkinson's disease (PD) and psychosis.Settings and Design:This was a prospective, cross sectional, hospital-based study done at the Department of Neurology, National Institute of Mental Health and Neurosciences, Bangalore, India from September 2009 to January 2011. All patients with PD, diagnosed by United Kingdom PD Society Brain Bank criteria, having with features of psychosis as diagnosed by the neuropsychiatric inventory (NPI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Three studies reported the proportion of AH that were verbal: Amar et al . (2014) found 11/18 (61.1%) of patents had verbal AH in PD; Fénelon et al . (2000) reported a similar proportion in PD – 13/21 (61.9%); while Suárez-González et al .…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…Three studies reported the proportion of AH that were verbal: Amar et al . (2014) found 11/18 (61.1%) of patents had verbal AH in PD; Fénelon et al . (2000) reported a similar proportion in PD – 13/21 (61.9%); while Suárez-González et al .…”
Section: Resultsmentioning
confidence: 97%
“…Fifteen studies (Fernandez et al ., 1992; Graham et al ., 1997; Fénelon et al ., 2000; Holroyd et al ., 2001; Gupta et al ., 2004; de Maindreville et al ., 2005; Pacchetti et al ., 2005; Papapetropoulos et al ., 2008; Williams et al ., 2008; Fénelon et al ., 2010; Mack et al ., 2012; Svetel et al ., 2012; Amar et al ., 2014; de Chazeron et al ., 2015; Llorca et al ., 2016) diagnosed PD according to a version of the United Kingdom Parkinson's Disease Society Brain Bank Criteria (Gibb and Lees, 1988). Five other studies used different diagnostic criteria, including definite or probable PD based on Larsen et al .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Pure hallucinations were commonest in these patients (85%) and a combination of delusions and hallucinations was found in 7.5%. [ 71 ] Of these visual hallucinations were predominant, amounting to 60%.…”
Section: Clinical Featuresmentioning
confidence: 99%